Metapsicologia dell’interpretazione - Baldini, Franco (Metapsychologica - rivista di psicanalisi freudiana, 2022)
This paper aims to show the deep connection between metapsychology and the technique of interpretation. Besides the subdivision between construction and interpretation, the motivations behind the use of the rule of free association will be understood. Evidence will also be provided of the fact that - contrary to the claims of many contemporary psychoanalysts - the Freudian interpretation procedure is a very sophisticated device, whose rules depend neither on a general sacralisation of the setting nor on intentions to safeguard the patient’s well-being. Indeed, it will be shown that the interpretation technique becomes a perfectly sterile tool if not subordinated to pretensions of objectivity and precise references to the psychic dynamics that metapsychological theory describes.